From Bees to Flies: Global Shift in Pollinator Communities Along Elevation Gradients - McCabe, Lindsie M.; Cobb, Neil S. (Frontiers in Ecology and Evolution, 2021)
Bees decrease in abundance and richness along elevation gradients, while flies replace bees as the dominant flower visitors in higher elevation systems. We reviewed the existing literature to determine if this global phenomenon of pollinator communities switching from bees to flies occurs at the same place along a temperature gradient. Here we examined five studies that have documented this bee-to-fly transition in the United States, Europe, and Australia. We determined where the bee-to-fly transition occurred along a temperature/elevation gradient for each study that ranged from 1.1 to 8.3°C. We found that pollinator communities shifted from bee dominated to fly dominated communities between 4.9 – 5.7 °C on all elevation gradients worldwide. This shift in pollinators could substantially impact ecological systems reliant on fly pollination as temperatures continue to warm.